2015
DOI: 10.3389/fpsyg.2015.01830
|View full text |Cite
|
Sign up to set email alerts
|

Odor Perception in Children with Autism Spectrum Disorder and its Relationship to Food Neophobia

Abstract: Atypical sensory functioning in Autism Spectrum Disorder (ASD) has been well documented in the last decade for the visual, tactile and auditory systems, but olfaction in ASD is still understudied. The aim of the present study was to examine whether children with ASD and neuro-typically (NT) developed children differed in odor perception, at the cognitive (familiarity and identification ability), sensorimotor (olfactory exploration) and affective levels (hedonic evaluation). Because an important function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…In addition, calories from carbohydrates, obtained through food records sustain this result. An important feature showed by ASD patients, which can be a barrier to widening food diversity, is food neophobia or preferring familiar foods (Luisier et al, 2015). Parents reported that almost 45% of ASD patients in our study never try new foods, and nearly 30% just sometimes do it, which corroborate for the limited food repertoire and probably for the subsequent nutrient deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calories from carbohydrates, obtained through food records sustain this result. An important feature showed by ASD patients, which can be a barrier to widening food diversity, is food neophobia or preferring familiar foods (Luisier et al, 2015). Parents reported that almost 45% of ASD patients in our study never try new foods, and nearly 30% just sometimes do it, which corroborate for the limited food repertoire and probably for the subsequent nutrient deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on identification evaluations reported opposite findings with altered identification abilities [Bennetto et al, ; Galle et al, ; Luisier et al, ; May et al, ; Tavassoli & Baron‐Cohen, ] as much as typical identification performances [Brewer et al, ; Dudova et al, ; Galle et al, ]. Regarding discrimination and odor rating, no difference appears in the only study using discrimination assessment [Galle et al, ] and some differences are reported in odor pleasantness in three other studies [Hrdlicka et al, ; Legiša et al, ; Luisier et al, ]. Some of studies have included males and females in their groups but they do not observed the gender‐related performances in the sensory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…We identified one study performing an odor discrimination test [Zatorre & Jones-Gotman, 1991] where there is no difference between their groups [Galle et al, 2013]. Finally, four studies perform pleasantness assessment giving opposite findings with differences in pleasantness rating of some odors in Hrdlicka et al [2011] and Luisier et al [2015] unlike in Galle et al [2013] and varying results in Legi sa, Messinger, Kermol, and Marlier [2013] with preserved intensity rating but differences appear with some odors that are rated less unpleasant in the HFA group. To our knowledge, few studies have been focusing on psychophysical assessment of gustation in individuals with ASD.…”
Section: Insarmentioning
confidence: 99%
“…Specifically sensory differences in processing in the proximal domains of touch and smell/taste have been shown to distinguish autism and non-autism groups (Schreck et al, 2004;Schreck and Williams, 2006;Leekam et al, 2007;Tomchek and Dunn, 2007), thereby potentially implicating sensory differences as a cause of food selectivity (Williams et al, 2000;Rastam, 2008;Twachtman-Reilly et al, 2008;Cermak et al, 2010). Indeed, specific contextual factors such as texture, taste, temperature, smell, and consistency of foods, have been reported to be associated with food selectivity (Whiteley et al, 2000;Williams et al, 2000;Schreck et al, 2004;Seiverling et al, 2010Seiverling et al, , 2011Kuschner et al, 2015;Luisier et al, 2015;Postorino et al, 2015). The growing body of evidence supporting the significant relationship between sensory differences and greater food selectivity not only in autistic individuals (Matson and Fodstad, 2009;Cermak et al, 2010;Nadon et al, 2011b;Suarez et al, 2012Suarez et al, , 2014bBeighley et al, 2013;Mazurek et al, 2013;Johnson et al, 2014;Zobel-Lachiusa et al, 2015;Chistol et al, 2018) but also in typically developing children (Farrow and Coulthard, 2012;Johnson et al, 2015;Coulthard et al, 2016) and those with an intellectual disability (Engel-Yeger et al, 2016) should not therefore be surprising.…”
Section: Sensory Approachmentioning
confidence: 99%